2023
DOI: 10.3390/ijerph20043387
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fintech Development on Air Pollution

Abstract: Over the past 40 years of reform and opening-up, China has achieved rapid economic and technological growth at the cost of severe air pollution. The emerging Fintech, as the result of financial institutions’ adapting to the latest digital technology, might be a solution to reduce air pollution. This paper investigates the impact of Fintech development on air pollution using a two-factor fixed effects model based on data for prefecture-level cities in China from 2011 to 2017. The findings show that Fintech deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, using the two-way fixed effects model, we find that digital financial development is significantly positively correlated with air pollution in the baseline result. After using the IV regression approach, the relationship of digital finance and air pollution changes to be negatively correlated, which is consistent with Ma et al ( 2023) [52]. We suggest that this difference in the baseline results is because the data are different.…”
Section: Literature Reviewsupporting
confidence: 88%
See 1 more Smart Citation
“…However, using the two-way fixed effects model, we find that digital financial development is significantly positively correlated with air pollution in the baseline result. After using the IV regression approach, the relationship of digital finance and air pollution changes to be negatively correlated, which is consistent with Ma et al ( 2023) [52]. We suggest that this difference in the baseline results is because the data are different.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Many researchers find that digital finance is environmentally friendly [52][53][54][55][56]. Ma et al (2023) investigate the impact of Fin-tech development on air pollution using a two-factor fixed effects model based on data for prefecture-level cities in China from 2011 to 2017, and show that Fin-tech development effectively reduces air pollution emissions [52].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study in Turkey showed that fintechs educate their users on sustainability issues, which helps promote responsible consumption and production [5]. A study in China shows the growth of fintechs alone can explain the reduction in sulfur dioxide and dust levels with an R-square of 93% and 88%, respectively [38]. Including other variables in the regression model does not change the R-square.…”
Section: Literature Review Of Green Fintechmentioning
confidence: 99%
“…Fintechs directly reduce environmental costs by providing digital finance and reducing the need to commute [38]. Instant payment fintechs replace cheques, credit cards, and cash [39].…”
Section: Literature Review Of Green Fintechmentioning
confidence: 99%
See 1 more Smart Citation